An investigation on 4-thiazolidinone derivatives as dual inhibitors of aldose reductase and protein tyrosine phosphatase 1B, in the search for potential agents for the treatment of type 2 diabetes mellitus and its complications. Issue 23 (15th December 2018) - Maccari, Rosanna; Del Corso, Antonella; Paoli, Paolo; Adornato, Ilenia; Lori, Giulia; Balestri, Francesco; Cappiello, Mario; Naß, Alexandra; Wolber, Gerhard; Ottanà, Rosaria
Graphical abstract: Highlights: 4-Thiazolidinones were synthesised and tested as dual AR/PTP1B inhibitors. SAR, molecular docking and kinetic studies were carried out. Two compounds endowed with interesting AR/PTP1B inhibition profiles were identified. Features useful to achieve simultaneous inhibition of both AR and PTP1B emerged. Abstract: Designed multiple ligands (DMLs), developed to modulate simultaneously a number of selected targets involved in etiopathogenetic mechanisms of a multifactorial disease, such as diabetes mellitus (DM), are considered a promising alternative to combinations of drugs, when monotherapy results to be unsatisfactory. In this work, compounds1 –17 were synthesized and in vitro evaluated as DMLs directed to aldose reductase (AR) and protein tyrosine phosphatase 1B (PTP1B), two key enzymes involved in different events which are critical for the onset and progression of type 2 DM and related pathologies. Out of the tested 4-thiazolidinone derivatives, compounds12 and16, which exhibited potent AR inhibitory effects along with interesting inhibition of PTP1B, can be assumed as lead compounds to further optimize and balance the dual inhibitory profile. Moreover, several structural portions were identified as features that could be useful to achieve simultaneous inhibition of both human AR and PTP1B through binding to non-catalytic regions of both target enzymes.